Implementing Blended Learning Toward Students’ Self Efficacy in Writing Class: Students and Teachers’ Voice - Jamila Hamidah; Ishak Said; Ratnawati . (Universitas Bengkulu, 2019)
This article reports on students' and teachers’ perceptions and of their self-efficacy on implementing blended learning in writing class. Self-efficacy has been defined as the belief we have in our own abilities, specifically our ability to meet the challenges and complete a task successfully (Akhtar, 2008).This research employed a survey study by means of questionnaire and interview. Fifty one of the third year students of English Department Galuh University were employed as participants. The result of this research showed that students’ self-efficacy improved after learning in writing classes on implementing blended learning, the students felt confident, enjoy the class, and then the students felt more motivated when learning. Furthermore, most of the students stated that self-efficacy was necessary, because it affected not only on implementing blended learning in writing class but also in the other courses. Each student has different self-efficacy, high and low self-efficacy that is able to influence how their learning achievement. it is recommended to further research that self-efficacy measurements must be far better and more accurate from various aspects. Thus the results would be certainly more relevant and detailed.